Geometric Analysis and PDEs Lectures given at the C.I.M.E. Summer School held in Cetraro, Italy, June 11-16, 2007 - Gursky, Matthew J.; Lanconelli, Ermanno; Malchiodi, Andrea; Tarantello, Gabriella; Wang, Xu-Jia; Yang, Paul C. (C.I.M.E. Foundation Subseries, 2009)
This volume contains lecture notes on some topics in geometric analysis, a growing mathematical subject which uses analytical techniques, mostly of partial differential equations, to treat problems in differential geometry and mathematical physics. The presentation of the material should be rather accessible to non-experts in the field, since the presentation is didactic in nature. The reader will be provided with a survey containing some of the most exciting topics in the field, with a series of techniques used to treat such problems.